The Relative Age Effect in invasion team sports: A systematic review in youth sports - Leandro Amancio Silva; Lucas Leonardo; Heitor de Andrade Rodrigues; Tathyane Krahenbühl (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The difference in birth dates between athletes of the same age can result in an advantage for the relatively older one. This is referred to as the relative age effect (RAE). This effect can interfere in the practice of children and youth athletes and can also influence their training and development to reach a high level of the sport. This study aimed to review previous research based on the following question: “What are the influences and consequences of the RAE in the sports practice of youth athletes in invasion team sports?” The method used was a systematic literature review based on the PRISMA method. The descriptors relative age effect AND sport were used on the CAPES Periodicals Portal and Pub Med platforms. After applying the inclusion and exclusion criteria and performing the necessary analyses, 82 articles were included in the study. It was found that the high competitive level, the sport’s popularity, coaches’ perception, and biological characteristics, primarily in the puberty period, have the greatest influence on the relative age effect and interfere in the permanence and sports careers of youth athletes.